2013
DOI: 10.1093/cid/cit638
|View full text |Cite
|
Sign up to set email alerts
|

Virological, Serological, and Antiviral Studies in an Imported Human Case of Avian Influenza A(H7N9) Virus in Taiwan

Abstract: We describe the clinical course and virological characteristics of the first H7N9 influenza case in a Taiwanese patient; this patient had detectable viruses in the airway for 2 weeks, during which time an oseltamivir resistance-associated R292K mutation rapidly emerged. Anti-H7N9 antibody was detected 21 days after onset of symptoms, when H7N9 viral load declined significantly.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
29
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 17 publications
0
29
0
Order By: Relevance
“…Because the H7N9 virus is resistant to M2 blockers, patients have been treated with neuraminidase (NA) inhibitors (NAIs), among which oseltamivir is the most widely used. Notably, evidence for a therapeutic effect of oseltamivir treatment was reported in H7N9-infected patients during the 2013 outbreak (2)(3)(4)(5). In early 2015, the first imported H7N9 cases in North America were described in two travelers returning from China; both patients were given oseltamivir and eventually recovered from the disease (6).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Because the H7N9 virus is resistant to M2 blockers, patients have been treated with neuraminidase (NA) inhibitors (NAIs), among which oseltamivir is the most widely used. Notably, evidence for a therapeutic effect of oseltamivir treatment was reported in H7N9-infected patients during the 2013 outbreak (2)(3)(4)(5). In early 2015, the first imported H7N9 cases in North America were described in two travelers returning from China; both patients were given oseltamivir and eventually recovered from the disease (6).…”
mentioning
confidence: 99%
“…In the early stage of the 2013 outbreak, A/Taiwan/1/2013 (H7N9) virus (Taiwan/1) was recovered from a patient who underwent two courses of oseltamivir treatment (2,4). In a single isolate, we identified four virus variants differing by a single amino acid in the NA compared to the wild-type (WT) virus (22).…”
mentioning
confidence: 99%
“…However, in October 2013 reports of new human H7N9 infections began to increase and, as of March 2014, more than 400 human infections leading to 115 deaths have been reported (2). Although the majority of human infections remain contained to mainland China, there have been imported cases confirmed in Taiwan, Hong Kong SAR, and Malaysia (3)(4)(5). There is no evidence that sustained human-to-human transmission is occurring, although the H7N9 viruses possess several key amino acid changes often associated with mammalian replication and transmission, heightening public health concerns (6)(7)(8).…”
mentioning
confidence: 99%
“…Patients infected with H7N9 viruses can exhibit severe and often lethal disease characterized by rapidly progressive pneumonia leading to acute respiratory distress syndrome and respiratory failure (4). Because of this, and its avian origin, the human H7N9 infections have been touted as an "H5N1-like" disease.…”
mentioning
confidence: 99%
“…Notably, no viral RNA could be detected in the serum specimens during the whole process, which did not fully corresponded with previous studies. Although Lin P et al also did not detect the viral RNA in a severe case [11], Hu Y et al reported that twelve out of fourteen H7N9-infected cases (86%) were positive in serum viral load test [8]. Based on the difference of admission, we believe that the viremia should be highly relevant with immunosuppression, which was mainly caused by the application of corticosteroid in Hu Y et al's study.…”
Section: Discussionmentioning
confidence: 71%